Validity and reliability of portable blood lactate analyzers: A systematic review with COSMIN and GRADE assessment - Bruno, J.; Thapa, R. K.; Santos, Â.; Montoro-Bombú, R.; Sarmento, H. (Sports Medicine - Open, 2026)
Background Portable blood lactate analyzers (PBAs) are increasingly used in sports and clinical contexts to assess physiological responses. Blood lactate is a critical biomarker for evaluating performance and metabolic thresholds. However, variability in device accuracy, sampling procedures, and calibration raises concerns about their validity and reliability.